A latent class analysis of psychotic symptoms in the general population. (June 2018) - Pignon, Baptiste; Peyre, Hugo; Szöke, Andrei; Geoffroy, Pierre A; Rolland, Benjamin; Jardri, Renaud; Thomas, Pierre; Vaiva, Guillaume; Roelandt, Jean-Luc; Benradia, Imane; Behal, Hélène; Schürhoff, Franck; et al.
Objective: Individuals with psychotic symptoms may actually correspond to various subgroups, characterized by different patterns of psychotic symptoms as well as specific sociodemographic and clinical correlates. We aimed to identify groups of individuals from the general population with specific patterns of psychotic symptoms. Methods: In a 38, 694-subject survey, a latent class analysis was performed to identify subgroups based on the distribution of seven psychotic symptoms taken from the Mini International Neuropsychiatric Interview. The different classes were subsequently compared according to sociodemographic and clinical correlates. Results: The best fit was obtained with a four-class solution, including the following: (1) a class with a low prevalence of all psychotic symptoms ('LOW', 85.9%); (2) a class with a high prevalence of all psychotic symptoms ('HAL + DEL', 1.7%); and classes with a high prevalence of (3) hallucinations ('HAL', 4.5%) or (4) delusions ('DEL', 7.9%). The HAL + DEL class displayed higher rates of history of trauma, social deprivation and migrant status, while the HAL and DEL classes displayed intermediate rates between HAL + DEL and LOW. HAL + DEL displayed the highest rates of psychotic and non-psychotic disorders and the use of mental health treatment, while HAL and DEL displayed intermediate rates of these disorders between HAL + DEL and LOW. In comparison to the HAL class, psychotic and substance use disorders were more frequent in the DEL class, while anxiety and mood disorders were less frequent. Conclusion: These findings support the hypothesis of a continuum model relating the level of psychotic symptoms to the level of global psychopathology.